DOSE MEASUREMENT OF TOTAL SCALP RADIATION TREATMENT USING LATERAL PHOTON-ELECTRON TECHNIQUE - LERTBUTSAYANUKUL, Chawalit; JUMPANGERN, Chotika; CHAROONSANTIKUL, Chulee; SANGHANGTHUM, Taweap; SURIYAPEE, Sivalee (The ASEAN Journal of Radiology, 2023)
Purpose: To find the optimal abut or overlap area between photon-electron field and to measure superficial and intracranial dose using lateral photon-electron technique of total scalp radiation treatment. Methods and Materials: CT scan of the Alderson Rando phantom was used in GE Target treatment planning system to find the optimal abut or overlap area between photon-electron fields. Each treatment fraction composed of two lateral-opposed fields of 6-MV photon (with square blocks) and two 9-MeV electron square fields. After the optimal plan was selected, film verification of the plan using solid water phantom instead of Alderson Rando phantom was performed. TLD chips were used to measure the intracranium and superficial skin dose of Alderson Rando phantom. Results: Abutting photon-electron field resulted in 9-12 mm wide cold area along the junction. To compensate for this cold area, 6 to 7-mm overlapping between photon and electron irradiated field was applied in phase I of treatment and no overlapping photon-electron was used in phase II. This resulted in more homogeneous dose distribution. Film verification of the plan showed concordant result with the treatment planning system. By using TLD measurement, the average doses at frontal lobe, corpus collosum and parietal lobe relative to prescribed dose were 19.2, 12.3 and 10.9%, respectively. The superficial skin doses at vertex and forehead relative to prescribed dose were 99 and 113.5%, respectively. Conclusion: Overlapping electron-photon field using square block in phase I and abutting electron-photon fields using square block in phase II were suggested as a useful technique to deliver homogeneous skin dose while avoiding the radiation dose to the underlying brain. The adaptability of the suggested photon block and electron insert has a great advantage and increases the convenience for clinical service. Since the distance between abutting and overlapping junction is very small, care must be taken in the setting up and the immobilization of the patient’s head in the treatment room.